Lessons Learned from the Livestock Master Plan and Future Investment Priorities for Animal Resources Development - CGIAR Initiative on National Policies and Strategies; International Livestock Research Institute (CGIAR Initiative on National Policies and Strategies, 2023)
This presentation slide is a collection of slides used by speakers on Mar. 9, 2023, during the Lessons Learned from the Livestock Master Plan and Future Investment Priorities for Animal Resources Development workshop/seminar. The event aimed to take stock of the LMP and livestock sector development more generally and explore future sector priorities. The event was co-organized by the International Food Policy Research Institute (IFPRI) and the International Livestock Institute (ILRI), as part of the CGIAR initiative on National Policies and Strategies (NPS) initiative and the IFPRI Rwanda Strategy Support Program and in collaboration with the Ministry of Agriculture and Animal Resources (MINAGRI).